Diagnosis of security conditions and occupational health in the tourism sector and Yopal livestock - Vargas Cardozo, Ivan Leonardo
The Tourism and Livestock Sector of Yopal has some special characteristics, among which the following stand out: the tourist activity focused as a source of income that contributes to the economic growth of the region and the perception that the employer has when implementing improvement strategies health and safety conditions as an expense that decreases the profitability of service provision, there is informality of the tourism sector in contracting for tasks and there is no affiliation to ARL and EPS, the degree of training that people who offer tourism services have it is minimal, safety and health conditions at work generate working conditions that can affect the actors, public health conditions for being an endemic area require a system that responds to the treatment of endemic diseases in the tourism sector. The work methodology focuses on obtaining the consolidated safety and health conditions in the work of the tourism sector of the municipality of Yopal, through a mixed approach the preparation of a crosssectional descriptive study, in which a analysis at a given time point of the information contained in the characterization studies prepared in order to identify and describe the variables related to sociodemographic characteristics and health and safety conditions at work in the companies of the tourism sector of the city of Yopal.